Multimorbidity and Quality of Life among Geriatric Population of Karachi Pakistan - Syed Hasan Danish, Farah Ahmad, Daniyal Fahad, Shaima Sultana Memon, Oam Parkash, Khushbakht Shoaib, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine association of quality of life and multimorbidity among geriatric population of Karachi Pakistan Methods: It was a cross sectional study conducted in district of Karachi district using cluster sampling technique. Sample had greater than 60 years of age restricting those with mental disorders, speech disorders or language barriers. Sample size was n=362. Data was collected using WOHQOL-BREF with four domains, social relationships, psychological health, physical health and environment domain. Data was collected by face to face interviews after informed consent keeping information confidential. p-value less than 0.05 was considered significant. For numerical data descriptive analysis was used and categorical data was expressed by frequency and percentages using SPSS version 24. Odds ratio was used to find association of multimorbidty and quality of life Results: Of total n=90 (25%) participants had none or single disease, with multimorbidity in n=272 (75%) participants. Most n=165 (46%) had hypertension, Diabetes was present in n=56 (16%). Bones and joints in n=133 (38%), Obesity in n=80(22%). Most n=144 (40%) rated their life quality as good, n=30 (8.3%) as very good, n=57 (15.5%) rated their quality of life as poor, n=3 (0.8%%) rated it very poor and remaining n=128(35.4%) were in between. Mean scores of Environmental domain had highest score then physical health, psychological domain and least for social domain. When association was seen in multimorbidity and life quality Environment domain displayed significant association with OR: 1.9 ( p value 0.009).In Environment and Social domain majority were found to be satisfied. Conclusion: Significant association was seen between Multimorbidity and Enviornmental domain in Quality of life. Keywords: Multimorbidity, Quality of life, Geriatrics